1981
DOI: 10.1016/s0006-3495(81)84742-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that dimers remaining in preinduced Escherichia coli B/r Hcr+ become insensitive after DNA replication to the extract from Micrococcus luteus

Abstract: In Escherichia coli B/r Her+ irradiated with two separate fluences, dimer excision is prematurely interrupted. The present study was designed to follow tha fate of dimers remaining unexcised. The results imply that these dimers (or distortions containing dimers) are transformed on replication from the state of sensitivity to the state of insensitivity to endonuclease from Micrococcus luteus. This conclusion is based on the following findings: (a) dimers were radiochromatographically detectable in DNA replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…This would indicate that there is some alteration in the structure of the duplex opposite the replicated pyrimidine dimer. A related observation was reported by two groups (31,32), who found that after replication of UV-irradiated DNA in vivo, in E. coli (31) 10 mM Tris HCl at pH 8, 10 mM EDTA, 0.1 M NaCl, bovine serum albumin at 0.1 mg/ml, and 2 x iOs units of T4 endonuclease V. Mixtures were incubated at 37°C for 60 min, after which they were analyzed by alkaline agarose gel electrophoresis as described in Materials and Methods and in the legend to Fig. 2A.…”
Section: Discussionsupporting
confidence: 75%
“…This would indicate that there is some alteration in the structure of the duplex opposite the replicated pyrimidine dimer. A related observation was reported by two groups (31,32), who found that after replication of UV-irradiated DNA in vivo, in E. coli (31) 10 mM Tris HCl at pH 8, 10 mM EDTA, 0.1 M NaCl, bovine serum albumin at 0.1 mg/ml, and 2 x iOs units of T4 endonuclease V. Mixtures were incubated at 37°C for 60 min, after which they were analyzed by alkaline agarose gel electrophoresis as described in Materials and Methods and in the legend to Fig. 2A.…”
Section: Discussionsupporting
confidence: 75%
“…This was also true when we tried to measure the amount of pyrimidine dimers in the unreplicated DNA (HH peak). This insensitivity of UV lesions to dimerspecific enzyme has already been reported for dimer-containing DNA in E. coli B/r DNA after replication (36). When these bacteria receive a sublethal UV dose before UV irradiation they do not efficiently excise the lesion.…”
Section: Methodssupporting
confidence: 64%